A systematic framework of vulnerability analysis of a natural gas pipeline network - Su, Huai; Zio, Enrico; Zhang, Jinjun; Li, Xueyi (Reliability engineering & system safety, 2018)
•A method is developed to analyze vulnerability of gas pipeline networks.•Supply capacity, gas grid performance and demand change are considered.•Indices are developed to measure gas grid vulnerability and pipeline criticality.•Demand site robustness is analyzed by statistics and topology properties.•The application of the method is studied in a complex natural gas pipeline network. A systematic framework is developed to assess the vulnerability of natural gas pipeline networks. To measure the impact of accidents on gas supply service, a consequence model is developed based on a flow algorithm embedded into an optimization scheme, with the consideration of physical constraints. The vulnerability analysis is performed from three viewpoints: global vulnerability analysis, demand robustness and critical pipeline analysis. The global vulnerability analysis is performed considering hazards and threats in gas sources, demand and transmission system. The analysis of demand robustness evaluates the capacities of demand sites to withstand the strains imposed on the pipeline network system and further explains the differences in capacities, from a graph theory perspective. In the critical pipeline analysis, criticalities of pipelines are evaluated by considering direct attacks and using a physical flow-based method. The analyses are performed on a relatively complex gas pipeline network taken from literature.